Integrasi Augmented Reality Cerita Rakyat untuk Penguatan Literasi Budaya dan Pengembangan Sumber Daya manusia Pendidikan - Honorata Ratnawati Dwi P; Dwi Putranti, Honorata Ratnawati; Englishtina, Inti; Pujiati, Listiyoni Meli (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2025)
This community service program aims to promote learning transformation through the implementation of Augmented Reality (AR) based on Indonesian folklore at SMP Stella Matutina, Salatiga. The activity was conducted collaboratively by lecturers from the fields of Human Resource Management and English Education, involving teachers and 89 students from grades VII and VIII. The program integrated local wisdom and digital innovation in the form of interactive learning media to enhance students’ cultural literacy and learning motivation. The implementation method included needs assessment, development of bilingual AR content (Indonesian–English), teacher training, and classroom application. The results indicated increased student engagement, improved teacher skills in educational technology, and enhanced student awareness of cultural preservation. Folklore-based AR media proved to be an effective and sustainable strategy for developing contextual and innovative educational human resources